2022
DOI: 10.1021/acsnano.2c00054
|View full text |Cite
|
Sign up to set email alerts
|

Optical Nanosensor for Intracellular and Intracranial Detection of Amyloid-Beta

Abstract: Amyloid-beta (Aβ) deposition occurs in the early stages of Alzheimer’s disease (AD), but the early detection of Aβ is a persistent challenge. Herein, we engineered a near-infrared optical nanosensor capable of detecting Aβ intracellularly in live cells and intracranially in vivo. The sensor is composed of single-walled carbon nanotubes functionalized with Aβ wherein Aβ-Aβ interactions drive the response. We found that the Aβ nanosensors selectively responded to Aβ via solvatochromic modulation of the near-infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 109 publications
0
17
0
Order By: Relevance
“…57 Here, we found that the injection of carbon nanotube sensors directly into the cerebellum results in a local extracellular pool of nanotubes in the brain. Extracellular accumulation of nanotube sensors has been reported following intracranial injections 37 and observed in ex vivo preparations. 35,36,61,62 Following intracerebral injection, the sensor localized in extracellular pools and responded in ASMKO mice by a decrease in the average center wavelength.…”
Section: T H Imentioning
confidence: 98%
“…57 Here, we found that the injection of carbon nanotube sensors directly into the cerebellum results in a local extracellular pool of nanotubes in the brain. Extracellular accumulation of nanotube sensors has been reported following intracranial injections 37 and observed in ex vivo preparations. 35,36,61,62 Following intracerebral injection, the sensor localized in extracellular pools and responded in ASMKO mice by a decrease in the average center wavelength.…”
Section: T H Imentioning
confidence: 98%
“…When a SWCNT is functionalized with versatile surface chemistry including smalls molecules, polymers, or DNA, SWCNT forms specific 3D corona interfaces that enable selective molecular recognition of target analytes (Figure b). , This molecular adsorption instantly changes the bandgap structure of SWCNTs, subsequently inducing variations in wavelength or intensity of fluorescence signal. Versatile constructs of this SWCNT based nanosensor have been designed and synthesized to detect a wide range of biochemical molecules of cells, ranging from small molecules such as ROS to large proteins such as interleukin-6 (IL-6) family cytokines and amyloid-beta, even extending to the plant hormone gibberellin. The nanosensors for the cellular target analytes are integrated within microchannels in a uniform array using the evaporation induced self-assembly (EISA) based on silane chemistry. ,, In the initial stages of NCC operation, excitation laser sources having visible light wavelength for the SWCNT fluorescence are exposed to the nanosensor array from the bottom side of the channel (Figure a). Each single cell flowing just below the nanosensor array is strongly interacting with nIR fluorescence from the array, where a highly focused propagating beam from the shadow-side of the cell is generated due to constructive interference of the light field, called a photonic nanojet (PNJ). , This PNJ phenomenon focuses light in a manner that treats each single cell as a specialized optical lens reflecting the physical characteristics of each single cell.…”
Section: New Class Of Single Cell Analytic Technology: Nanosensor Che...mentioning
confidence: 99%
“…Single-walled carbon nanotubes (SWCNTs) benefit from unique optical and electronic properties, which render them favorable fluorescent probes for imaging, sensing, and biomedical applications, owing to their fluorescence in the near-IR range where tissue, blood, and biological samples in general are mostly transparent. Moreover, SWCNT sensors are stable at room temperature, provide spatiotemporal information, and do not photobleach upon use, unlike many other fluorescent sensors. The mechanism of SWCNT-based sensors usually relies on tailored functionalization of the nanotube surface, which mediates the interaction with the analyte of interest, such that binding of the target molecule results in a modulation of the emitted fluorescence. Fluorescent SWCNT sensors were applied for the biosensing of different analytes and enzymes. ,,,, These range from monitoring progesterone and cortisol in vivo (mice), fibrinogen and insulin in blood and cell culture, , nitroaromatics and pathogens , in vivo (plants), volatiles in the gaseous phase, to enzymatic activity. …”
Section: Introductionmentioning
confidence: 99%
“… 38 41 Fluorescent SWCNT sensors were applied for the biosensing of different analytes and enzymes. 23 , 29 , 31 , 37 , 42 50 These range from monitoring progesterone and cortisol in vivo (mice), 31 fibrinogen and insulin in blood and cell culture, 45 , 48 nitroaromatics 29 and pathogens 49 , 51 in vivo (plants), volatiles in the gaseous phase, 52 to enzymatic activity. 53 55 …”
Section: Introductionmentioning
confidence: 99%